2019
DOI: 10.1002/ird.2373
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts and Adaptation for Crop Management of Winter Wheat and Maize in the Semi‐arid Region of Iran

Abstract: Climate change is expected to lead to declining crop yields in semi‐arid regions due to higher temperatures and more severe droughts, which calls for adaptations in crop management. We used the WOFOST and AquaCrop crop simulation models to examine the response of crop yield in winter wheat and maize to a set of climate change scenarios up to 2040 in the semi‐arid climate of Mashhad in north‐east Iran. Modelled climate change from six AOGCMs including GFCM21, HADCM3, INCM3, IPCM4, MPEH5 and NCCCSM under IPCC SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…To sum up, for the studied variables (annual ET 0 , monthly ETc, yield, biomass and CO 2 assimilation), the trends predicted in this work would match in a regional scale what other studies have observed: A northward movement of crop suitability zones, as well as increased crop productivity in Northern Europe [69]. Furthermore, the simulations suggest that there is a greater potential for adaptation in northern, cooler zones, in which the reduction in yields can be compensated by shifting the crop growing season to cooler months [30], by advancing sowing, and by taking advantage of an extended growing period through the use of suitable varieties [70].…”
Section: Biomass and Cosupporting
confidence: 84%
See 2 more Smart Citations
“…To sum up, for the studied variables (annual ET 0 , monthly ETc, yield, biomass and CO 2 assimilation), the trends predicted in this work would match in a regional scale what other studies have observed: A northward movement of crop suitability zones, as well as increased crop productivity in Northern Europe [69]. Furthermore, the simulations suggest that there is a greater potential for adaptation in northern, cooler zones, in which the reduction in yields can be compensated by shifting the crop growing season to cooler months [30], by advancing sowing, and by taking advantage of an extended growing period through the use of suitable varieties [70].…”
Section: Biomass and Cosupporting
confidence: 84%
“…crop, the region and the chosen adaptation strategies, such as matching crops to soils [29]. Other strategies such as shifting the sowing date, changing the required cultivar growth duration, the development of heat tolerant plants may have to be adopted depending on the location and crop, as noted by Khordadi et al [30]. Concerning the study presented herein, an important point that should be taken into consideration is that the yield simulations generated by the model in 2050 and 2070 involve changes in the crop cultivation period.…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the need to increase food production, some researchers have warned that climate change may reduce global food production in the coming decades. Climate change will positively or negatively affect the yields of crops grown commercially in the many regions of the world where they are produced, depending on the severity and type of these changes [11][12][13][14][15][16][17]. Future climate change, associated with land use change and population growth, will put global food security at risk and increase malnutrition, especially in lessdeveloped countries [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another main agricultural challenge is increasing agricultural yield and decreasing agricultural greenhouse gas (Headey et al 2010). With the increase in the population globally, the agricultural system needs to raise its production capacity (Isik and Devadoss 2006;Khordadi et al 2019). These subsequent pusses the excessive use of pesticides and fertilizers, and other resources to increase agricultural greenhouse gas emissions (Molua 2009;Yu et al 2018).…”
Section: Introductionmentioning
confidence: 99%